Processes of Airway Remodeling in Children with Bronchial Asthma on the Background of Intracellular Infections - O.Ye. Chernyshova (Zaslavsky O.Yu., 2015)
This article provides information about the processes of airway remodeling in children with bronchial asthma. There are described the changes in the levels of matrix metalloproteinases, tissue inhibitor of matrix metalloproteinase, transforming growth factor, autoantibodies to collagen type III, endothelin-1 in bronchial asthma in children, uninfected and infected with intracellular infections caused by herpes simplex virus types I-II, cytomegalovirus, Epstein-Barr virus, Сhlamydophila pneumoniae and Mycoplasma pneumoniae.